Equações diferenciais ordinárias lineares com coeficientes constantes e derivação da equação característica - Santos, Ricardo da Silva (2015)
This work was divided into three chapters , the rst we have some basic de nitions for the study of di erential equations, and basic results as Euler's formula and Wronskian . In the second chapter, we talked about Di erential Equations of First Order Linear, and commenting on PVI, and the Theorem of Existence and Uniqueness for ODEs. In the third and main chapter, we work with resolution methods Di erential Equations. In particular, we present a unnusual in mathematics literature to solve Linear Di erential Equations, which is by Equation Characteristic.